Environmentally Benign Oxidation of Aniline with 30 % H2O2 Catalyzed by Some Heteropolyoxometalates - Tayebee, Reza (Asian Journal of Chemistry, 2010)
Oxidation of aniline with 30 % hydrogen peroxide catalyzed by different heteropolyoxometalates of tungeston and molybdenum under air at room temperature is studied. Findings showed that aniline was converted into nitroso-benzene in water, as well as in CH2Cl2, with good yields and high selectivities.